Heat transfer enhancement in tube by inserting uniform/non-uniform twisted-tapes with alternate axes: Effect of rotated-axis length - Eiamsa-Ard, S.; Somkleang, P.; Nuntadusit, C.; Thianpong, C. (My University, 2013)
Heat transfer enhancement in a tube using twisted tapes with alternate axes at different alternate lengths (in term of alternate length to twist length ratio, l/y = 0.5, 1.0, 1.5 and 2.0) has been investigated in the present work. The twisted tapes with both uniform and non-uniform alternate lengths (TAs and N-TAs) as well as a typical twisted tape (TT) were comparatively tested for Reynolds number between 5000 and 21,500. The experimental results revealed that all the TAs and N-TAs yielded higher Nusselt number and friction factor than the TT and the Nusselt number and friction factor obtained were considerably increased with decreasing the alternate length (l). Heat transfer and friction factor by the N-TAs were found to be directly dependent of alternate length rather than the variation of the length. In the present study, the optimum tradeoff between the enhanced heat transfer and increased friction was found by using the TA at l/y = 0.5, giving the highest heat transfer rate as well as the maximum thermal performance factor. In addition, empirical correlations for Nusselt number, friction factor and performance evaluation criteria to assess the real benefits in using the TAs/N-TAs of the enhanced tube were also determined. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Friction; Heat transfer enhancement; Non-uniform twisted-tape with alternate axis; Swirl flow; Twisted-tape